From MEFs to Matrigel 2: Splitting hESCs from MEFs onto Matrigel - Khvorostov, Ivan (MyJove Corporation, 2008)
This video demonstrates how to grow human embryonic stem cells (hESCs) on mouse embryonic fibroblast (MEF) feeder cells, how to passage hESCs from MEF plates to feeder cell-free Matrigel plates.